Enhanced Thermal Stability of W‐Ni‐Al2O3 Cermet‐Based Spectrally Selective Solar Absorbers with Tungsten Infrared Reflectors. Issue 2 (11th September 2014) - Cao, Feng; Kraemer, Daniel; Sun, Tianyi; Lan, Yucheng; Chen, Gang; Ren, Zhifeng
<x xml:space="preserve">Abstract</x> Solar thermal technologies such as solar hot water and concentrated solar power trough systems rely on spectrally selective solar absorbers. These solar absorbers are designed to efficiently absorb the sunlight while suppressing re‐emission of infrared radiation at elevated temperatures. Efforts for the development of such solar absorbers must not only be devoted to their spectral selectivity but also to their thermal stability for high temperature applications. Here, selective solar absorbers based on two cermet layers are fabricated on mechanically polished stainless steel substrates using a magnetron sputtering technique. The targeted operating temperature is 500–600 °C. A detrimental change in the morphology, phase, and optical properties is observed if the cermet layers are deposited on a stainless steel substrate with a thin nickel adhesion layer, which is due to the diffusion of iron atoms from the stainless steel into the cermet layer forming a FeWO4 phase. In order to improve thermal stability and reduce the infrared emittance, tungsten is found to be a good candidate for the infrared reflector layer due to its excellent thermal stability and low infrared emittance. A stable solar absorptance of ≈0.90 is demonstrated, with a total hemispherical emittance of 0.15 at 500 °C.